Multilayer Strategies Incorporating Natural Bactericide for Titanium Surface Functionalization - Carolina Cruz Ferreira; Ingrid Zavarize Evangelista Vieira; Carla Sérgio Barboza; Andrés Vercik; Luci Cristina de Oliveira Vercik; Daniela Sachs; Neide Aparecida Mariano (Materials Research)
Current development of hybrid and bioactive materials based on consolidated metallic substrates, such as titanium and its alloys, combined with polymeric and ceramic additives has been promoted. These materials, with an emphasis on hydroxyapatite and polycaprolactone, have a high applicability in tissue replacement and regeneration. Since bacterial contamination and biofilm formation are the main causes of post-surgical complications involving implants, the present work proposes a hybrid coating to address these issues. It incorporates Melaleuca alternifolia essential oil as a natural bactericide, into a polymeric PCL layer. This layer was applied over a bioceramic coating on a commercially pure titanium substrate. The surface evolution of the apatite layer was verified through bioactivity tests in simulated body fluid, verifying a homogeneous layer with appreciable globular morphology. In the microbiological assays by disk-diffusion against Staphylococcus aureus and Escherichia coli, the formation of small halos was observed for both cultures. As a result, it is suggested that the proposed hybrid coating may improve the osseointegration process and biocompatibility, indicating the potentiality of prosthetic application in orthopedic medical devices.